Intermittent fasting in osteoarthritis: from mechanistic insights to therapeutic potential - Sun, Nianyi; Zhao, Yinuo; Wang, Junyu; Zhang, Anren; He, Yu (Frontiers in Nutrition, 2025)
Osteoarthritis (OA) is a prevalent whole-joint disease characterized by cartilage degradation, subchondral bone remodeling, synovial inflammation, and systemic metabolic dysregulation, imposing significant health and socioeconomic burdens globally. Conventional treatments primarily offer symptomatic relief without addressing the underlying disease mechanisms. Recently, intermittent fasting (IF), defined by cyclic caloric restriction and metabolic switching, has emerged as a promising lifestyle intervention with therapeutic potential for OA. Preclinical and preliminary clinical studies suggest that IF beneficially impacts OA pathogenesis by improving metabolic profiles, reducing systemic and local joint inflammation, activating cellular protective autophagy pathways, and positively modulating the gut microbiota. This review systematically synthesizes current mechanistic insights, preclinical findings, and emerging clinical evidence regarding IF’s role in OA prevention and treatment. We also address practical considerations for implementing IF in clinical practice and outline future research priorities necessary to validate and optimize IF protocols tailored for OA management.